Development of polymeric nanomedicine for accelerating tissue regeneration and biological activity assessment of antimicrobial components - Gupta, Prem Shankar (IIT(BHU) Varanasi, 2024)
Abstract is available in the attachment.
Keywords: Biomedical Engineering